Evaluation of SCUBE-1 Level and Carotid Intima Media Thickness in Recurrent Pregnancy Loss - Sabri Colak; Emine Seda Guvendag Guven; Suleyman Guven; Turan Erdogan; Yeşim Bayoglu Tekin; Funda Akpınar (Ankara Medical Journal, 2020)
INTRODUCTION: Evaluation of the signal peptide complement C1r/C1s, Uegf, and Bmp1 (CUB), and epidermal growth factor-like domain-containing protein-1 (SCUBE-1) levels and carotid intima media thickness (CIMT) between the group of patients with and without recurrent pregnancy loss (RPL). METHODS: This prospective and single-center study included 20-40-year-old 30 patients with and 30 patients without a history of RPL. No patients with any anatomical, hereditary, or endocrinological thrombophilic defects were included. Comparison of SCUBE-1 levels and CIMT were made between the patient and control groups. RESULTS: There were no statistically significant differences between patients and control groups in terms of demographic characteristics except for gravidity, parity and miscarriages.The mean SCUBE-1 level in the RPL group was statistically significantly higher compared to the control group (16.44+-5.43 vs.10.17+-5.19, respectively, p=0.001). The mean CIMT value in RPL patients was statistically significantly higher than that of the control group (0.60+-0.09 vs.0.44+-0.07, respectively, p=0.001). DISCUSSION AND CONCLUSION: High levels of serum SCUBE-1 and CIMT in RPL may suggest that ischemia and endothelial dysfunction may be involved in the etiology of RPL. Future studies may shed light on the diagnosis, treatment, and management of RPL.